Hubungan Gaya Kepemimpinan Kepala Madrasah dengan Kinerja Tenaga Kependidikan: (Penelitian di MAN Kota Bandung dan Kota Cimahi) - Vanesha, Tantia; Lestari, Ambar Sri; Supendi, Pepen (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
This research aims to describe the reality of the leadership style of Madrasah heads and the performance of MAN education staff in Bandung City and Cimahi City and analyze the relationship between the two. The research uses a quantitative approach with correlational descriptive methods. The data collection technique is distributing questionnaires with analysis techniques using SPSS 26 to analyze instruments (validity and reliability), descriptive statistical analysis, assumption analysis (normality and linearity) and inferential statistics in the form of coefficient correlation tests. The research results explain that variable It can be concluded that the leadership style of the Madrasah head is considered good. Variable Y has a normal data distribution and the result of calculating the partial average of the indicators in the variable is 3.23 in the